HUBUNGAN ANTARA LOCUS OF CONTROL INTERNAL DENGAN KEMATANGAN KARIR PADA SISWA SMK N 1 BANTUL - Widyastuti, Ninik; Widyowati, Arini (HUMANITAS, 2015)
AbstractThis study aims to determine the relation between internal locus of control and career maturity of students in vocational high school (SMK) Negri 1 Bantul. The research involved 150 eleventh-grade students of five classes in SMK Negri 1 Bantul as samples that were chosen using cluster random sampling. Data was collected using career maturity scale and internal locus of control scale and Pearson Product Moment correlation technique with SPSS 16.0 for Windows was used to analyze the data. The results showed that the coefficient correlation between those two variables reach at r = 0.161 and p = 0.049 (p <0.05= significant). It can be concluded that there is a significant positive relationship between internal-locus of control and students’s career maturity. The higher students’ internal locus of control, the higher students’ career maturity and vice versa. Keywords: career maturity, career-planning, internal locus of control.